A Randomized Controlled Trial Comparing Microthin Descemet Stripping Automated Endothelial Keratoplasty With Descemet Membrane Endothelial Keratoplasty: Two-Year Report. Issue 12 (8th December 2022) - Pujari, Rathin; Matsou, Artemis; Kean, Jane; Zhang, Jufen; Rajan, Madhavan S.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to report the 2-year outcomes of a double-blinded randomized controlled trial comparing Descemet membrane endothelial keratoplasty (DMEK) and microthin Descemet stripping automated endothelial keratoplasty (MT-DSAEK). Methods: Fifty-six eyes of 56 patients were randomized to DMEK or microthin DSAEK (MT-DSAEK). The main outcome measure was best spectacle-corrected visual acuity (BSCVA) at 24 months. Other secondary outcomes included complications, endothelial cell density, and vision-related quality-of-life (vQoL) scores. Results: There was no statistically significant difference in BSCVA between the DMEK and MT-DSAEK groups at the 2-year time point (mean ± SD; 0.04 ± 0.14 vs. 0.12± 0.19, P = 0.061) in contrast to the 1-year results (mean ± SD; 0.04 ± 0.13 vs. 0.11 ± 0.09, P = 0.002) previously reported. Endothelial cell density did not show a statistically significant difference at 24 months between the DMEK and MT-DSAEK groups (1522 ± 293 cell/mm 2 vs. 1432 ± 327 cells/mm 2, P = 0.27). There were 2 additional graft rejection episodes in the MT-DSAEK group between the 1- and 2-year follow-up periods, but this did not result in graft failure. The mean vQoL scores between DMEK and MT-DSAEK indicated similar patient satisfaction between the groups (97.1 ± 4.0 vs. 92.6 ± 10.2, P = 0.13). Conclusions: In summary, the trial showed no significant difference in BSCVA at 24 months between the DMEK and MT-DSAEK groups. Both techniques continued to demonstrate comparable outcomes for complication rates, endothelial cell loss, and patient-reported vQoL scores. Trial Registration: ISRCTN10578843.